Phosphorus spectroscopy in acute TBI demonstrates metabolic changes that relate to outcome in the presence of normal structural MRI. Issue 1 (January 2020) - Stovell, Matthew G; Mada, Marius O; Carpenter, T Adrian; Yan, Jiun-Lin; Guilfoyle, Mathew R; Jalloh, Ibrahim; Welsh, Karen E; Helmy, Adel; Howe, Duncan J; Grice, Peter; Mason, Andrew; Giorgi-Coll, Susan; et al.
Metabolic dysfunction is a key pathophysiological process in the acute phase of traumatic brain injury (TBI). Although changes in brain glucose metabolism and extracellular lactate/pyruvate ratio are well known, it was hitherto unknown whether these translate to downstream changes in ATP metabolism and intracellular pH. We have performed the first clinical voxel-based in vivo phosphorus magnetic resonance spectroscopy ( 31 P MRS) in 13 acute-phase major TBI patients versus 10 healthy controls (HCs), at 3T, focusing on eight central 2.5 × 2.5 × 2.5 cm 3 voxels per subject. PCr/γATP ratio (a measure of energy status) in TBI patients was significantly higher (median = 1.09) than that of HCs (median = 0.93) (p < 0.0001), due to changes in both PCr and ATP. There was no significant difference in PCr/γATP between TBI patients with favourable and unfavourable outcome. Cerebral intracellular pH of TBI patients was significantly higher (median = 7.04) than that of HCs (median = 7.00) (p = 0.04). Alkalosis was limited to patients with unfavourable outcome (median = 7.07) (p < 0.0001). These changes persisted after excluding voxels with > 5% radiologically visible injury. This is the first clinical demonstration of brain alkalosis and elevated PCr/γATP ratio acutely after major TBI. 31 P MRS has potential for non-invasively assessing brain injury in the absence of structural injury, predicting outcome and monitoring therapy response.